(untitled) (Vietnam Journal of Agriculture and Environment, 2024)
Drought stress is an abiotic factor affecting maize production. This study was conducted to examine if the growth and development of four maize varieties would be affected by the different water deficit conditions under the vinyl house condition. The experiment was designed using a randomized complete block design (RCBD). The water deficit conditions with four levels were 30% w/w as the control, 25% w/w, 20% w/w and 15% w/w. The maize varieties were CP111, LCH9, NK7328 and NK4300. The results showed that regardless of maize varieties, the reduction of soil water content caused to suppressing maize growth, which led to a decrease of grain yield of maize varieties. The best plant performance was observed in the treatment of 30% w/w of soil moisture content (as control condition), which followed by treatment of 25% w/w of soil moisture content. The lowest growth traits, physiological traits (leaf area, shoot dry weight), yield components, grain yield of maize were observed in plants treated by 15% w/w of soil moisture content (drought stress condition). In particular, NK4300 showed significantly higher physiological traits and grain yield than those of other varities under control condition (30% w/w). However, under drought stress conditions (25% to 15% w/w), LCH9 and NK7328 showed significantly higher physiological traits and grain yield than those of NK430. This result suggests that water deficit condition effect on growth and development of four maize varieties, but the extent of effect of water deficit condition on growth and yield of corn depends on the different maize varieties.